Enhancing Usability of the Academic Information System at Bhayangkara University: A Design Thinking and System Usability Approach - Rakhmi Khalida; R Wisnu Prio Pamungkas (LPPM Universitas Islam 45 Bekasi, 2023)
Bhayangkara University implements an information system to assist its academic process, namely SIA (Academic Information System). The high level of usability in SIA affects the smooth running of the academic process. This research uses a combination of design thinking and system usability scale methods as an approach to increase usability in AIS applications. The results show that the SIA application has a high usability value with a B rating scale and the good acceptable category is pleasant for users. Recommendations for improvements based on the method used are increasing server capacity so that SIA can work more relevantly, and effectively, and can use last a long time